PENGARUH PERIKLANAN, BEBAS ONGKOS KIRIM DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN BARANG PADA APLIKASI LAZADA DI KECAMATAN RANGKUI KOTA PANGKALPINANG - Ajang Ajang; Hasanuddin Hasanuddin (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to analyze the effect of advertising, free shipping, and service quality on purchasing decisions on the Lazada application in the city of Pangandaran. The population used in this study are consumers who buy goods on the Lazada application in Rangkui District, Pangkal Pinang City. A sample of 96 respondents was determined by the accidental sampling technique. The research instrument is a questionnaire. The results of this study indicate that the influence of advertising, free shipping, and service quality simultaneously affect purchasing decisions on the Lazada application in Rangkui District, Pangkalpinang City. A partial test (t-test) shows that 1) Advertising variable has a significant effect on purchasing decisions on Lazada applications in Rangkui District, Pangkalpinang City.